Five-Membered-Ring-Fused Tacrines as Anti-Alzheimer’s Disease Agents - Carreiras, Maria do Carmo; Marco-Contelles, José (Synlett, 2021)
Our endeavors in the design, synthesis, and biological assessment of five-membered-ring-fused tacrines as potential therapeutic agents for Alzheimer’s disease are summarized. Particularly, we have identified racemic 4-(2-methoxyphenyl)-3-methyl-2,4,6,7,8,9-hexahydropyrazolo[4′,3′:5,6]pyrano[2,3-b]quinolin-5-amine, a pyranopyrazolotacrine, as having the best nontoxic profile at the highest concentrations used (300 μM); this allows cell viability, is less hepatotoxic than tacrine, and is a potent noncompetitive AChE inhibitor (IC50 = 1.52 ± 0.49 μM). It is able to completely inhibit the EeAChE-induced Aβ1–40 aggregation in a statistically significant manner without affecting the Aβ1–40 self-aggregation at 25 μM, and shows strong neuroprotective effects (EC50 = 0.82 ± 0.17 μM).1 Introduction2 Furo-, Thieno-, and Pyrrolotacrines3 Pyrazolo-, Oxazolo-, and Isoxazolotacrines4 Indolotacrines5 Pyrano- and Pyridopyrazolotacrines6 Conclusions and Outlook
Keywords: Alzheimer’s disease; acetyl(butyryl)cholinesterase enzymes; acetyl(butyryl)cholinesterase inhibitors; Friedländer reactions; tacrines; multitarget small molecules